Generation of transgene-free induced pluripotent stem cells from cardiac fibroblasts of goat embryos - Hanna, Mira (J Stem Cells Regen Med, 2020)
Induced pluripotent stem cells (iPSCs) hold a great potential for therapeutic regenerative medicine. The aim of this study was to generate induced pluripotent stem cells from goat embryonic cardiac tissue derived fibroblasts. The isolated cardiac fibroblasts from the cardiac tissue of goat embryos were positive for alfa smooth muscle actin, vimentin and discoidin domain receptor2. From these cells, we generated transgene free iPSCs using piggyBac transposons / transposase using five transcription factors (Oct4, Sox2, Klf, Myc and Lin 28). The generated iPSCs were SSEA1, SSEA4 and Oct4 positive. They were cultured on neofeeders using 20% Serum replacement – IMDM with bFGF. They could form cystic and compact embryoid bodies that showed differentiated ectodermal and mesodermal like cells when cultured using 20% FBS-IMDM without bFGF. The iPSCs, generated in the frame of this approach were produced without the use of integrating virus and the reprogramming transgenes were removed at the end of the process. Though there were limitations in the approach used, a substantial sign of reprogramming was obtained.